Carybdea branchi, sp. nov., a new box jellyfish (Cnidaria: Cubozoa) from South Africa - Gershwin, Lisa-Ann; Gibbons, Mark J. (Zootaxa, 2009)
A common and conspicuous member of the medusan fauna of South Africa has been the subject of repeated taxonomic confusion. After having been mistakenly identified by earlier workers as either Carybdea alata or Tamoya haplonema, this large and colourful carybdeid is described herein as Carybdea branchi, sp. nov. It is distinguished from its congeners on numerous characters: body to about 8cm in life, densely scattered with nematocyst warts over the whole body and abaxial keels of the pedalia; a bulge or lateral thorn on the pedalial canal bend; with 2 dendritic velarial canals per octant, highly diverticulated; with a long manubrium; with greatly bushy epaulette-like phacellae, comprising 20 or more roots tightly clustered; with well developed mesenteries; and with conspicuous brownish pigmented areas over the proximal and distal regions of the pedalia and over the phacellae. A comparative table of the primary diagnostic characters of species in the genus Carybdea is given.